Analysis of Iterated Affine Transformation Function and Linear Mapping for Content Preservation - Garg, Ankit; Negi, Ashish; Chauhan, Geeta (International Journal of Engineering and Technology, 2018)
In image scaling contents of image can be distorted which are required to preserve using linear mapping. Geometric transformations can preserve structural properties i.e. parallelism, colinearity and orientation. It is highly desirable to preserve structural properties of image contents because human visual system is very sensitive to distortion of objects. In this paper image scaling is performed using iterative affine transformation and results show that linear mapping function applied on affine space preserve affine properties under affine transformation. A number of scaling operations are applied on image using iterative affine transformation and for each iteration linear mapping is performed to preserved object structure. Analysis present in this paper shows that in image scaling preservation of image content is possible under iterative affine transformation and linear mapping. Image artifacts can be minimize using saliency based antialiasing algorithm after affine transformation.Â Â